Building supply chain collaboration on SMEs: The role of ICT and trust - Titik Kusmantini; Agung Satmoko; Krisnandini Wahyu Pratiwi; Arum Kurniawati (Jurnal Siasat Bisnis, 2020)
This study aims to investigate the relationship between information and communication technology (ICT), trust, and supply chain collaboration and their impact on companies' operational performance. Partial Least Square (PLS) was used to test the research models. A survey was conducted to collect data from screen-printing SME, which is one of the leading creative industries, in Yogyakarta. Questionnaires were directly distributed and collected from 48 SMEs. The results show that trust and ICT have a significant and direct effect on supply chain collaboration and operational performance. The indirect effect of ICT and trust on operational performance through supply chain collaboration also prove to be significant. The practical implication of this research is the importance of SMEs understanding of the strategic role of technology in sharing information, because with ICT, companies will be able to build more effective business communication. Besides, it is also important to understand the role of trust as a factor supporting the companies' commitment to building sustainable cooperation and achieving higher operational performance.